2018
DOI: 10.1007/s11892-018-0973-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies for the Management of Type 1 Diabetes in Pregnancy

Abstract: Purpose of Review The purpose of the study is to discuss emerging technologies available in the management of type 1 diabetes in pregnancy. Recent Findings The latest evidence suggests that continuous glucose monitoring (CGM) should be offered to all women on intensive insulin therapy in early pregnancy. Studies have additionally demonstrated the ability of CGM to help gain insight into specific glucose profiles as they relate to glycaemic targets and pregnancy outcomes. Despite new studies comparing insulin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
(52 reference statements)
0
6
0
3
Order By: Relevance
“…More widely, a recent review of technology in diabetes pregnancy highlighted uncertainty regarding the benefits of pump usage in terms of HbA1c and pregnancy outcomes. 5 Closed-loop systems represent the latest stage in diabetes technology evolution, building on established technologies such as CGM and CSII but seeking to reduce the cognitive burdens required for effective use of sensor-augmented pump therapy. Closed-loop systems utilize control algorithms to provide automated, CGM-responsive basal insulin delivery via an insulin pump every 10-15 minutes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More widely, a recent review of technology in diabetes pregnancy highlighted uncertainty regarding the benefits of pump usage in terms of HbA1c and pregnancy outcomes. 5 Closed-loop systems represent the latest stage in diabetes technology evolution, building on established technologies such as CGM and CSII but seeking to reduce the cognitive burdens required for effective use of sensor-augmented pump therapy. Closed-loop systems utilize control algorithms to provide automated, CGM-responsive basal insulin delivery via an insulin pump every 10-15 minutes.…”
mentioning
confidence: 99%
“…More widely, a recent review of technology in diabetes pregnancy highlighted uncertainty regarding the benefits of pump usage in terms of HbA1c and pregnancy outcomes. 5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, there were significant changes in glucose management that include an increase in the use of insulin pumps and CGMs. Previous studies examining the efficacy of these techniques showed conflicting results [ 23 27 ]. We did not demonstrate any changes in mean HbA1C levels before and during pregnancy and the percentage of women with higher than recommended levels of HbA1c during pregnancy remained fairly high at 60–70%.…”
Section: Discussionmentioning
confidence: 99%
“…További vizsgálatok szükségesek annak eldöntésére, hogy e rendszerrel elérhető-e az a glikémiás kontroll, amely a terhességi szövődmények megelőzéséhez szükséges. 38…”
Section: Inzulinpumpa Cgms Szenzorhoz Integrált Inzulinadagolásunclassified